Dampak Sosial Ekonomi, Budaya terhadap Keberhasilan Pengelolaan Sumber Daya Laut di Pulau Terluar Kabupaten Natuna - Syahdanur; Hasim As’ari (Jurnal Ekonomi KIAT, 2018)
The condition of the people in the outer islands is far from development connectivity, and the limited touch of development, making the condition and economy of the community do not experience development so as not to support the economic progress of the community so that this study raises the social, economic and cultural conditions of the community to achieve successful management of marine resources. This research was conducted in Natuna Regency, especially the people in Outermost Islands, using qualitative research methods to describe the natural phenomenon of research so that it can describe the actual conditions. The results of the study illustrate that social, economic, cultural conditions influence the success of management of marine resources, so that planning becomes a policy that is consistent with the conditions and needs of the community. To achieve successful management of marine resources must be in accordance with the conditions of human resources where the policy will be determined.